A comparative study of collagenase ointment versus povidone-iodine dressing in non-healing ulcers - Bhedi, Amul; Panchal, Mithun; Patel, Hitesh; Sarkar, Arnab (International Surgery Journal, 2017)
Background: The aim of the study was to evaluate effect of collagenase ointment and povidone-iodine on non-healing ulcer in the form of duration of ulcer covered with red granulation tissue and total hospital stay. Methods: The Study was conducted on 80 patients admitted in Surgery Department, SSG Hospital and Medical College Baroda, Gujarat, India during November 2006 to October 2008. All ulcers due to trauma, chronic ulcer or infected ulcer following debridement and incision and drainage were included in this study. In group A were wounds dressed in collagenase ointment and in group B were wounds dressed in povidone-iodine ointment till second surgery or complete healing. All data from both groups were collected and analyzed by chi-square test. Results: In this study, there was no difference in age distribution (p=0.62, p>0.05) with similar male to female ratio in both groups and also no significant difference in distribution of wounds size in both groups (p=0.92, p>0.05). Average size of wound in group A was 43 sq. cm and group B was 44 sq. cm. The significant difference was seen on floor of ulcer by healthy granulation which came on an average of within 11days in group A and within 18 days in group B (p=0.005, p<0.05). There was also a significant difference in average hospital stay, which was 25 days in group A and 35 days in group B (p=0.01, p<0.05). Conclusions:Collagenase ointment is clinically more efficient as a topical dressing and lowers the morbidity by reducing the hospital stay and the duration of dressing by promoting healing in non-healing wounds than povidine-iodine ointment.